Innovation box as a tax instrument of stimulating of innovation activities: the world experience - Ibrayeva, A. Zh. (Journal of Economic Research & Business Administration, 2015)
The article considers ways to stimulate innovation in the developed countries. The author analyzed the fi scal instrument stimulation of innovation activity “innovation box”, providing preferential taxation results of the use of intellectual property rights. This article provides an example of an “innovation box”, and described the use of of this benefi t. Also in the article, determined the effectiveness of this benefi t in the foreign experience. The author suggests that the benefi ts of “innovation box” make it an attractive instrument of tax stimulation of innovation in our country.